Multiple Introductions of the Asian Longhorned Tick (Haemaphysalis longicornis) to the United States Revealed Using Mitogenomics - Zoe E. Narvaez; Andrea M. Egizi; Michael J. Yabsley; Alec T. Thompson; Mohamed Moustafa; Erika Alt; Matthew Bickerton; Kim Bjorgo; Rebecca A. Butler; Alexandra Cumbie; Gillian Eastwood; Richard C. Falco; et al. (Ecology and Evolution, 2025)
ABSTRACT The Asian longhorned tick (ALT), Haemaphysalis longicornis, is a three‐host hard tick native to East Asia. Its opportunistic feeding habits make it an acute agricultural and medical threat, capable of spreading various zoonotic pathogens. An affinity for livestock and companion animals has allowed parthenogenetic populations of ALT to travel to and establish in overseas locations including the United States. To better understand the population dynamics of this rapidly expanding species, we sequenced the complete mitogenome of specimens collected from native and invasive ranges and performed phylogeographic analyses. As well as illustrating the diversity of Australasian and US ALT haplotypes, these methods have allowed us to estimate the source and frequency of successful introductions to the US. We highlight four potential introductions of parthenogenetic ALT, with likely origin populations identified in the Republic of Korea and Japan. These findings provide insight into potential routes of entry for ALT and other invasive tick species.